A comprehensive review of electrocoagulation for water treatment: Potentials and challenges. (15th January 2017) - Moussa, Dina T.; El-Naas, Muftah H.; Nasser, Mustafa; Al-Marri, Mohammed J.
Abstract: Electrocoagulation is an effective electrochemical approach for the treatment of different types of contaminated water and has received considerable attention in recent years due its high efficiency in dealing with numerous stubborn pollutants. It has been successful in dealing with organic and inorganic contaminants with negligible or almost no generation of by-product wastes. During the past decade, vast amount of research has been devoted to utilizing electrocoagulation for the treatment of several types of wastewater, ranging from polluted groundwater to highly contaminated refinery wastewater. This paper offers a comprehensive review of recent literature that has been dedicated to utilizing electrocoagulation for water treatment, focusing on current successes on specific applications in water and wastewater treatment, as well as potentials for future applications. The paper examines such aspects as theory, potential applications, current challenges, recent developments as well as economical concerns associated with the technology. Most of the recent EC research has been focusing on pollutant-specific evaluation without paying attention to cell design, process modeling or industrial applications. This review attempts to highlight the main achievements in the area and outlines the major shortcomings with recommendations for promising research options that can enhance the technology and broaden its range of applications. Highlights: A comprehensive review of electrocoagulation (EC) has been carried out. The review focuses on current successes and potentials for future applications. The paper examines EC theory, current challenges, and recent developments. The paper reviews the economic concerns associated with EC technology. Recommendations have been offered for promising research areas in EC technology.